Afroperipheral indigeneity in Wayde Compton’s The Outer Harbour - Cucarella-Ramón, Vicent (International Journal of English Studies, 2021)
Black Canadian writer Wayde Compton’s short story collection The Outer Harbour (2015) is located in the Afroperiphery of British Columbia which stands as a ‘contact zone’ that enables the alliances between Black and Indigenous peoples and also establishes a fecund ground of possibilities to emphasize the way in which cross-ethnic coalitions and representations reconsider imperial encounters previously ignored. The stories participate in the recent turn in Indigenous studies towards kinship and cross-ethnicity to map out the connected and shared itineraries of Black and Indigenous peoples and re-read Indigeneity in interaction. At the same time, the stories offer a fresh way to revisit Indigeneity in Canada through the collaborative lens and perspective of the Afroperipheral reality. In doing so, they contribute to calling attention to current cross-ethnic struggles for Indigenous rights and sovereignty in Canada that rely on kinship and ethnic alliances to keep on interrogating the shortcomings of the nation’s multiculturalism.